Cross-Sectional Study as Research Design in Medicine - Legiran; Puspa Zuleika (Archives of The Medicine and Case Reports, 2022)
A cross-sectional study is an observational study that analyzes data from a population at one point in time. These studies are often used to measure prevalence in medicine, analyze health studies, and describe health characteristics. Unlike other types of observations, in a cross-sectional study, each research subject was only observed once, the measurement of research variables was carried out at the time of the observation, and no follow-up was carried out on the measurements made. These studies are less expensive and easier to perform and help establish preliminary evidence in planning further studies in the future. This article reviews essential characteristics, describes strengths and weaknesses, discusses methodological issues, and provides design recommendations and statistical analysis for cross-sectional studies.